Mobile Cooling : Assessment of Challenges and Options - Ayres, Michael (World Bank, Washington, DC, 2020)
This paper provides background on the issue of cooling in land transportation applications including road, rail and refrigerated container shipping. The paper analyzes the impacts of mobile cooling on energy demand, carbon emissions, economic and development issues. It also considers how mobile cooling demand will grow over time under constrained and un-constrained conditions. Additionally, the paper aims to outline technologies that could reduce the impact of mobile cooling provision and the policies that are in place to encourage take-up and efficiency. Lastly, the paper highlights the remaining policy gaps and recommendations for policy action to advance mobile cooling access and reduce its impact on the environment.